Separation of Polyphenol Oxidase and its Inhibitor from Onion Leaves on Lignin Column - S. Goswami-Giri*, Anita; A. Sawant, Neha (Asian Journal of Chemistry, 2011)
Tyrosine is a key compound of pigmentation/browning reaction through the action of polyphenol oxidase. Discrimination of this pigmentation reaction is responsible for various types of diseases and disorders. Core part of enzyme, polyphenol oxidase is same; therefore to regulate such discriminations of pigmentations/browning, searching for nontoxic endogenous inhibitor of this activity is important in developing the rational chemotherapy of pigmentation. Polyphenol oxidase and endogenous inhibitor was purified on natural matrix. Endogenous inhibitor eluted in two fractions which contains 2.15 ± 0.04 % of flavanoid and 6.1 mg/12.20 % of vitamin C. Fraction I (UV 245 nm, m.w. 66KDa) inhibits 100 % polyphenol oxidase at 14 min while fraction II (UV 224.5 nm, m.w. 98 KDa) inhibits polyphenol oxidase at 18 min. It was also confirmed by TLC.